A conserved motif in human BTG1 and BTG2 proteins mediates interaction with the poly(A) binding protein PABPC1 to stimulate mRNA deadenylation. Issue 12 (2nd December 2021) - Amine, Hamza; Ripin, Nina; Sharma, Sahil; Stoecklin, Georg; Allain, Frédéric H; Séraphin, Bertrand; Mauxion, Fabienne
ABSTRACT: Antiproliferative BTG/Tob proteins interact directly with the CAF1 deadenylase subunit of the CCR4-NOT complex. This binding requires the presence of two conserved motifs, boxA and boxB, characteristic of the BTG/Tob APRO domain. Consistently, these proteins were shown to stimulate mRNA deadenylation and decay in several instances. Two members of the family, BTG1 and BTG2, were reported further to associate with the protein arginine methyltransferase PRMT1 through a motif, boxC, conserved only in this subset of proteins. We recently demonstrated that BTG1 and BTG2 also contact the first RRM domain of the cytoplasmic poly(A) binding protein PABPC1. To decipher the mode of interaction of BTG1 and BTG2 with partners, we performed nuclear magnetic resonance experiments as well as mutational and biochemical analyses. Our data demonstrate that, in the context of an APRO domain, the boxC motif is necessary and sufficient to allow interaction with PABPC1 but, unexpectedly, that it is not required for BTG2 association with PRMT1. We show further that the presence of a boxC motif in an APRO domain endows it with the ability to stimulate deadenylation in cellulo and in vitro . Overall, our results identify the molecular interface allowing BTG1 and BTG2 to activate deadenylation, a process recently shown to be necessary for maintaining T-cell quiescence. GRAPHICAL ABSTRACT: uf0001